A Randomized, Crossover Pilot Study of a Novel Web-Based/Mobile Platform for Collaborative Small Group Practice in Therapeutic Reasoning. (November 2020) - Gruenberg, Katherine; Brock, Tina; Garcia, Joshua; MacDougall, Conan
Background and Purpose: Therapeutic reasoning—the mental process of making judgments and decisions about treatment—is developed through acquisition of knowledge and application in actual or simulated experiences. Health professions education frequently uses collaborative small group work to practice therapeutic reasoning. This pilot study compared the impact of a web-based/mobile tool for collaborative case work and discussion to usual practice on student perceptions and performance on questions designed to test therapeutic knowledge and reasoning. Methods: In a therapeutics course that includes case-based workshops, student teams of 3 to 4 were randomly assigned to usual workshop preparation (group SOAP sheet) or preparation using the Practice Improvement using Virtual Online Training (PIVOT) platform. PIVOT was also used in the workshop to review the case and student responses. The next week, groups crossed over to the other condition. Students rated favorability with the preparatory and in-workshop experiences and provided comments about the PIVOT platform via a survey. Student performance on examination items related to the 2 workshop topics was compared. Results: One hundred and eleven students (94%) completed post-workshop surveys after both workshops. The majority of students (57%) preferred using the PIVOT platform for workshop collaboration. Favorability ratings for the in-workshop experience did not change significantly from first to second study week, regardless of sequence of exposure. There was no relationship between examination item scores and the workshop platform the students were exposed to for that content ( P  = .29). Student responses highlighted the efficiency of working independently before collaborating as a group and the ability to see other students' thought processes as valuable aspects of PIVOT. Students expressed frustration with the PIVOT user interface and the lack of anonymity when discussing their answers in the workshop. Conclusion: A web-based/mobile platform for student team collaboration on therapeutic reasoning cases discussed in small group settings yielded favorable ratings, examination performance comparable to standard approaches, and was preferred by a majority of students. During the rapid shift to substantial online learning for the COVID-19 pandemic, virtual collaboration tools like PIVOT may help health professions teachers to better support groups working virtually on scaffolded therapeutic reasoning tasks.